2011
DOI: 10.1007/s12262-010-0205-2
|View full text |Cite
|
Sign up to set email alerts
|

A Large Primary Hydatid Cyst of Thigh: A Case Report

Abstract: Primary hydatid disease of musculoskletal system is rare. A 60 year old woman presented with soft swelling in medial aspect of thigh, of long duration which was gradually increasing in size. She was initially diagnosed as lipoma of thigh, but ultrasonography revealed to be a cystic swelling suggestive of hydatid disease. MRI further reinforced the diagnosis. However serologic test (ELISA) was negative. Patient was given albendazole preoperatively. The swelling was removed en bloc and advised for adjunctive alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…According to the endemicity of HD in Iran, these two cases were diagnosed having primary HD of the breast and muscle. The diagnosis of HD should be considered when a palpable, painless mass which gradually increases in size over months or years, in endemic areas [ 11 , 12 ]. It might mimic fibroademoma, phyllodes tumor, chronic abscess, or even malignancies, and this should be included in the differential diagnoses of breast lumps, especially in endemic regions [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the endemicity of HD in Iran, these two cases were diagnosed having primary HD of the breast and muscle. The diagnosis of HD should be considered when a palpable, painless mass which gradually increases in size over months or years, in endemic areas [ 11 , 12 ]. It might mimic fibroademoma, phyllodes tumor, chronic abscess, or even malignancies, and this should be included in the differential diagnoses of breast lumps, especially in endemic regions [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current case reported positive history of animal contact without fulfilling any preventive measure. Up to date, 17 cases of HD of the thigh have been reported in the literature [ 2 , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. The age ranged between 8 to 61 years [ 12 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection in toto is the definitive management strategy [ 10 ]. The hydatid cysts in this case were managed under general anesthesia by two incisions, an elliptical one in the thigh and lower transverse pelvic incision.…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal hydatid disease is primary or secondary in origin. When primary location is the liver, lung or subphrenic region, secondary musculoskeletal involvement is an important possibility [8]. The diagnosis is mostly according to clinical symptoms, which may even take 5 to 20 years to establish; as Ghanaati et al reported such organ involvement for the knee, secondary to a liver hydatid disease after nine years [3].…”
Section: Discussionmentioning
confidence: 99%